On the measurement of high-energetic neutrinos with the IceCube neutrino telescope and with acoustic detection methods - Schunck, Matthias (Publikationsserver der RWTH Aachen University, 2011)
Neutrino astronomy is a new field of astroparticle physics that uses neutrino detectors to observe astrophysical objects. Over the last few decades, several dedicated neutrino telescopes have been built and several other are planned for the near future. In this thesis, two subjects have been addressed to enhance the detection of astrophysical neutrinos with the existing IceCube neutrino telescope as well as to explore new detection methods, namely the acoustic detection. In the first part of this thesis, the determination of the acoustic attenuation length in South-Pole ice is presented. This is part of a feasibility study to investigate the acoustic neutrino detection as a possibility to enhance the detection of the highest-energy neutrinos. For this, the acoustic properties of the ice have to be known, and the South-Pole Acoustic Test Setup (SPATS) has been built to determine these. The attenuation length is determined using in-situ measurements with SPATS and a retrievable transmitter (pinger), which was deployed in a depth between 190 and 500m into the water-filled drilling holes. The setup of these measurements allowed for a data sample with few systematic effects. Even though, the unknown angular-dependent sensitivities of the SPATS sensor channels cannot be avoided and are considered as the dominant systematic effect for these measurements. In this thesis, the acoustic attenuation length is calculated by comparing the energy contents of the pinger pulses recorded by the various SPATS sensor channels for different distances between the pinger and the respective channel. The energy was calculated from the Fourier spectra of the pinger pulses for a frequency range between 5 and 35 kHz. The attenuation coefficient is calculated for each channel individually and the weighted mean over the distribution of all considered channels leads to an attenuation length of 264(+52 -37)m. The dependence of the attenuation on both depth and frequency has been investigated, showing no indications for either. This result is ...